CNS changes in interstitial cystitis/painful bladder syndrome - Khavari, Rose (Nat Rev Urol, 2015)
Brain white matter (axonal) abnormalities associated with interstitial cystitis/bladder pain syndrome in women suggest that neuropathological brain alterations exist in, and might contribute to, chronic pelvic pain syndromes. Advancing our knowledge of central neuropathic mechanisms, which might initiate and/or maintain these syndromes, will help target pain-related neuroplasticity and identify future treatments.